ANTIMICROBIAL ACTIVITY OF Zingiber officinale ON TWO EMERGING PERIODONTOPATHOGENS: A LITERATURE REVIEW (REMUNOM, 2024)
Recent studies have verified the relationship between two bacteria and periodontal disease, namely Klebsiella pneumoniae and Escherichia coli. These microorganisms are treated as potential periodontopathogens or “emerging periodontopathogens”. The objective of this study was to perform a literature synthesis on the use of Zingiber officinale against two bacteria recently associated with the pathogenesis of periodontal disease: Klebsiella pneumoniae and Escherichia coli. A bibliographic survey was carried out in the Pubmed/Medline and Scopus databases to gather studies published between 2014 and 2024, including 13 articles with different methodologies. Escherichia coli has been associated with the etiology of periodontitis in studies evaluating Brazilian patients, in addition to K. Pneumoniae having been found in abundance in patients with non-mild periodontitis. The evaluated phytotherapeutic agent has an anti-inflammatory effect, controls gingival bleeding, and reduces pain after basic periodontal therapy. Thus, it was possible to verify a relationship between Klebsiella pneumoniae and Escherichia coli with periodontal disease, with the use of Zingiber officinale being effective in combating these microorganisms, with results indicating positive levels of antibiotic/anti-inflammatory action at the same level as other therapeutic alternatives already established and used for the same purpose.